Constructing an alternative concept of Islamic governance: a ‘maqasidic-consequentialism’ approach - Malik, Maszlee (2016)
The common perception of Islamic governance is a dark image of a non-democratic and autocratic system, or a dictatorship with iron claws, or the governance of the cleric elite with the infringement of people’s freedom under the banner of religion. This is mainly due to the fiqhi ‘legal positivistic’ framework that often used to explain issues concerning governance by mostly traditionalist and Islamicist scholars. Humanistic governance based on the preservation of the dignity of human beings, which has been the focal point in Islamic tenets, the inviolability of life, and responsible freedom should be explored and promoted as another alternative voice of the dominating conventional fiqhi ‘legal positivistic’ hegemony. Thus, a new ijtihad (reasoning) in dealing with the subject is absolutely mandatory. This paper will look into a new approach to governance from the ‘consequentialistic’ approach inspired by the general theory of Maqasid al-Shari’ah. This research will explore some conceptual grounds for the exploration by looking into epistemological dimension of governance from Islamic sources and principles through ‘inductive qualitative method’ to critically analyse the texts, as part of the deconstruction of discourse.